2019
DOI: 10.18632/aging.102429
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic genes in the tumor microenvironment in cervical squamous cell carcinoma

Abstract: Cervical squamous cell carcinoma (CSCC) is one of the most commonly occurring gynecological malignancies. Because CSCC is a biologically heterogeneous disease, its prognosis varies. Therefore, identifying prognostic biomarkers that reflect its biological heterogeneity could lead to better interventions for patients with a poor prognosis. This study used the ESTIMATE algorithm to identify immune related prognostic genes within the tumor microenvironment of CSCC. The results revealed that high immune scores were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 35 publications
0
34
0
Order By: Relevance
“…Indeed, as demonstrated in previous studies, HPV-positive tumors could be heavily infiltrated with leukocytes (both lymphocytes, and myeloid cells), with the microenvironment they contribute to characterized as inflammatory, wound-healing (proangiogenic) and immunosuppressive [75,85,111,[118][119][120][121]. At the same time, many other studies have documented the link between higher immune score or greater lymphocyte infiltration (especially CD8) with better overall survival in patients with advanced cervical cancer, and with regressing disease-in patients with high-grade intraepithelial lesions, supporting an important role of lymphocyte-mediated immunity for controlling the disease [111,121,122]. Although the factors underlying quantitative and qualitative characteristics of the immune (particularly, lymphocytic) infiltrate present in cervical tumors are the subject of special investigations and were not the task of the current research, nevertheless stratification of the FLT4, MET, and SLUG expression values in accordance with the amount of tumor-infiltrating lymphocytes resulted in more homogenous groups.…”
Section: Discussionmentioning
confidence: 91%
“…Indeed, as demonstrated in previous studies, HPV-positive tumors could be heavily infiltrated with leukocytes (both lymphocytes, and myeloid cells), with the microenvironment they contribute to characterized as inflammatory, wound-healing (proangiogenic) and immunosuppressive [75,85,111,[118][119][120][121]. At the same time, many other studies have documented the link between higher immune score or greater lymphocyte infiltration (especially CD8) with better overall survival in patients with advanced cervical cancer, and with regressing disease-in patients with high-grade intraepithelial lesions, supporting an important role of lymphocyte-mediated immunity for controlling the disease [111,121,122]. Although the factors underlying quantitative and qualitative characteristics of the immune (particularly, lymphocytic) infiltrate present in cervical tumors are the subject of special investigations and were not the task of the current research, nevertheless stratification of the FLT4, MET, and SLUG expression values in accordance with the amount of tumor-infiltrating lymphocytes resulted in more homogenous groups.…”
Section: Discussionmentioning
confidence: 91%
“…Li et al found that four IRGs were identified as the biomarkers to predict the prognosis for breast cancer (35). Pan et al discovered that 149 immune genes were identified as the prognostic genes in tumor IME to predict ESCC prognosis (36). Yang et al suggested that the diagnostic immune score (DIS) and prognostic immune score (PIS) showed diagnostic and prognostic significance for cancers in the digestive system (37).…”
Section: Discussionmentioning
confidence: 99%
“…To further understand the TME of cutaneous melanoma, the ESTIMATE algorithm was utilized to access immune and stromal status and found out effective prognostic immune-associated biomarkers [18]. In addition, another study suggested that high immune scores were closely associated with the better overall survival rate of cancer patients, implying the importance of TME in patient prognosis [13].…”
Section: Discussionmentioning
confidence: 99%
“…Also, with the advent of the big data era in which abundant transcriptome pro les and detailed clinical information of cancer patients could be obtained from public database such as The Cancer Genome Atlas (TCGA), bioinformatics-based analysis has become more and more widespread. Until now, ESTIMATE algorithm has been applied to an array of tumors including thyroid cancer [10], bladder cancer [11], hepatocellular carcinoma [12], and cervical squamous cell carcinoma [13] with high e cacy, providing valuable information for the diagnostic and prognostic assessment of cancer patients.…”
Section: Introductionmentioning
confidence: 99%